Validation of the Child-Oral-Health-Impact-Profile among adolescents in Johannesburg: A cross-sectional study - Yolanda Malele-Kolisa; Innocent Maposa; Veerasamy Yengopal; Jude Igumbor (African Journal of Primary Health Care & Family Medicine, 2023)
Background: Oral health-related quality of life (OHRQol) is described as the effect of oral conditions on the overall functioning and well-being of individuals.